IMPLEMENTASI PENGELOLAAN DANA DESA DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DI KAMPUNG KEMIRI DISTRIK MAKKI KABUPATEN LANNY JAYA - Etius Kogoya; Beatus Tambaip (Universitas Cenderawasih, 2021)
The purpose of this study is to find out how the implementation of Village Fund management in Kemiri Village, Makki District, Lanny Jaya Regency, to find out how productive economic business is in Kemiri Village, Makki District, Lanny Jaya Regency. And to find out whether the implementation of Dana Desa (DD) management in Kemiri Village can improve the community's economy. This study aims to analyze the implementation of Village Fund Management in Improving the Community Economy in Kemiri Village, Makki District, Lanny Jaya Regency in 2020 and analyze the obstacles that hinder the implementation of Village Fund Management in Improving the Community Economy in Kemiri Village in 2020. The author uses qualitative research methods with 10 key informants and data sources in the form of documents and researchers as research instruments to obtain data that meets the requirements in writing this scientific paper. The results of this study indicate that: a). Implementation of Village Fund Management in Improving the Community Economy in Kemiri Village, Lanny Jaya Regency in 2020, which includes indicators: Effectiveness, Efficiency, Adequacy, Equity, Responsiveness and Accuracy has been going well, although there are still people who are not satisfied with the implementation of the Village Fund program in improve the economy of the people in Kemiri Village in 2020. b). The obstacles to implementing Village Fund management in Improving the Community Economy in Kemiri Village, Makki District include: psychological constraints on the distribution of village funds that are not in accordance with technical guidelines/or lacking, the market field is difficult to predict for external markets, political constraints of the Regency Government, District Government, Government The village is not consistent in the funding ceiling available for serious realization in the village but there is budget politics, the village government's authority does not run optimally, practical political factors during the election are a measure of the distribution of village funds, resource constraints all SPJ (Surat Pertanggung Jawaban) is regulated by District Government because the Human Development Index in Kemiri Village is still low in special skills, there is no reality, this can be seen in the realization of the distribution budget for non-physical village funds, which is more than for physical development.